(untitled) (Atti del Sodalizio Glottologico Milanese, 2025)
This paper deals with the expression of plurality in Thai, a classifier language part of the controversial Tai-Kadai family. Although it does not present a specific morphological mark of number, as it is usually the case in classifier languages, Thai has four main morpho-syntactic strategies to express plurality. Apart from the bare nouns, which could function as singular or plural, Thai speakers may use reduplication, albeit only on a limited number of lexical entities, the insertion of the morpheme phûak ‘group’, and the creation of a complex noun structure with either a general quantifier or a numeral. These different strategies will be presented by stressing their correlation with the syntactic structure of the noun phrase and the relation between the number/quantifier and the classifier, by arguing that these strategies correspond to different types of plural markers.